Implementation of Ex-Erfpacht Land Redistribution in Wangunreja Village, Nyalindung Sub-District, Sukabumi District in 2025 - Kustiawan, Dian; Nur, Tuah; Fajar FY. Basori, Yana (Lafadz Jaya Publisher, 2025)
This research is entitled “Implementation of Ex-Erfpacht Land Redistribution in Wangunreja Village, Nyalindung District, Sukabumi Regency, 2025”. The object of this study is the ex-erfpacht land redistribution policy implemented by the local government and the National Land Agency. The purpose of this study is to understand the overall implementation of the land redistribution policy, including its process, challenges, and impact on the community. This study uses a descriptive qualitative method with the implementation model by Van Metter and Van Horn. Data collection techniques include observation, interviews, and document studies. The results show that the implementation of land redistribution in Wangunreja Village has been relatively effective. The policy standards are clear, the objectives are well understood, and the implementers respond positively. Although there are technical obstacles such as limited resources and difficult geographic conditions, the policy continues with strong inter-agency communication and active community participation. In conclusion, the ex-erfpacht land redistribution in Wangunreja Village has had a positive impact on legal land certainty and community welfare, showing strong synergy between policy implementers and beneficiaries.